2017
DOI: 10.1007/s00425-017-2713-9
|View full text |Cite
|
Sign up to set email alerts
|

The epigenetic memory of temperature during embryogenesis modifies the expression of bud burst-related genes in Norway spruce epitypes

Abstract: Main conclusion Epigenetic memory affects the timing of bud burst phenology and the expression of bud burst-related genes in genetically identical Norway spruce epitypes in a manner usually associated with ecotypes. In Norway spruce, a temperature-dependent epigenetic memory established during embryogenesis affects the timing of bud burst and bud set in a reproducible and predictable manner. We hypothesize that the clinal variation in these phenological traits, which is associated with adaptation to growth und… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
60
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 53 publications
(62 citation statements)
references
References 70 publications
1
60
0
1
Order By: Relevance
“…; Carneros et al . ), further studies are needed to confirm this. An increase in minimum and mean temperatures during the reproductive period seems to have more influence than increasing maximum temperature during the reproductive period in oak seedlings.…”
Section: Discussionmentioning
confidence: 92%
See 2 more Smart Citations
“…; Carneros et al . ), further studies are needed to confirm this. An increase in minimum and mean temperatures during the reproductive period seems to have more influence than increasing maximum temperature during the reproductive period in oak seedlings.…”
Section: Discussionmentioning
confidence: 92%
“…For example, in Norway spruce, Carneros et al . () found that an epigenetic memory mechanism affects both the timing of bud burst phenology and the expression of bud burst‐related genes in genetically identical Norway spruce epitypes (clones only differing in an epigenetic alteration in a gene), allowing them to adapt rapidly to a changing environment. The temperature sum experienced by the developing embryo and photoperiod conditions during embryogenesis epigenetically shift the growth cycle of the embryos, giving rise to different epitypes from the same genotype (Yakovlev et al .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…> 2 years for many pine species) present more opportunities for suboptimal temperatures to reduce seed quality [4]. Heat experienced by parental plants and directly by seeds can reduce seed viability and seedling vigor [3,9], and maladaptively affect progeny bud burst phenology and cold hardiness [17]. And while effects of elevated temperature during tree seed development have been studied with clones in temperature-controlled greenhouses [18], and by inferring temperature differences during seed development based on provenance climates [19], there is a dearth of knowledge of the consequences of warming during seed development in ecologically-realistic settings.…”
Section: Introductionmentioning
confidence: 99%
“…Majada et al (2001) suggested that in vitro development and germination are controlled by genes, although they are highly affected by environmental conditions, which can be manipulated (von Aderkas et al 2008(von Aderkas et al , 2015. Additionally, the temperature during multiplication and embryo maturation has been observed to have a delayed effect (epigenetic memory) on, e.g., survival, height growth and bud set in Norway spruce (Kvaalen and Johnsen 2008;Carneros et al 2017).…”
Section: Introductionmentioning
confidence: 99%